Early maternal and paternal caregiving moderates the links between preschoolers' reactivity and regulation and maturation of the HPA‐immune axis. Issue 5 (11th January 2021) - Abraham, Eyal; Zagoory‐Sharon, Orna; Feldman, Ruth
Abstract: While early caregiving and child's temperamental dispositions work in concert to shape social‐emotional outcomes, their unique and joint contribution to the maturation of the child's stress and immune systems remain unclear. We followed children longitudinally from infancy to preschool to address the buffering effect of early parenting on the link between temperamental dysregulation and hypothalamic–pituitary–adrenal (HPA)‐immune axis in preschool‐aged children. Participants included 47 typically developing children and their 94 parents in both mother‐father and two‐father families followed across the first 4‐years of family formation. In infancy, we observed parent‐infant synchrony and measured parental oxytocin; in preschool, we observed temperamental reactivity and self‐regulation and assessed children's cortisol and secretory Immunoglobulin A (s‐IgA), biomarkers of the stress and immune systems. Greater self‐regulation and lower negative emotionality were associated with lower baseline s‐IgA and cortisol, respectively. However, these links were defined by interactive effects so that preschoolers with low self‐regulation displayed higher s‐IgA levels only in cases of low parent‐infant synchrony and negative emotionality linked with greater baseline cortisol levels only when parental oxytocin levels were low. Results emphasize the long‐term stress‐buffering role of the neurobiology of parental care, demonstrate comparable developmental paths for mothers and fathers, and delineate the complex developmental cascades to the maturation of children's stress‐management systems.